Assessment of Osteoporosis Markers among Post-Menopausal Women at Sabratha Teaching Hospital, Western Libya - Bushra Mohamed, Siddig; Salih Elmahdi,; Al Basher Alafi,; Abdelkarim Abdrabo,; Shaima Almarnagi,; Aheid Rahoma,; Muna Shuhan, (AlQalam Journal of Medical and Applied Sciences, 2025)
Osteoporosis is a prevalent health issue that primarily affects older women and is characterized by reduced bone mass and an increased risk of fractures, particularly among postmenopausal women. This study aimed to assess osteoporosis markers—including serum calcium, parathyroid hormone (PTH), vitamin D levels, and bone mineral density (BMD) via DEXA scan—among postmenopausal women at Sabratha Teaching Hospital, western Libya. A descriptive, analytical, community-based study was conducted on 40 postmenopausal women aged >45 to 70 years at Sabratha Teaching Hospital between June and November 2023. Serum calcium levels were measured using a fully automated spectrophotometer (Model 4040), while PTH and vitamin D levels were assessed using the Cobas e411 analyzer. BMD was evaluated using dual-energy X-ray absorptiometry (DEXA scan) at Al-Shroug Medical Center in Tripoli. Demographic and biochemical data were analyzed using the Statistical Package for the Social Sciences (SPSS), version 25. Among the participants, 42.5% had normal serum calcium levels, and 57.5% had normal PTH levels. Notably, 92.5% (37 out of 40) of the women exhibited vitamin D deficiency. Additionally, 65% were found to have osteoporosis based on DEXA scan results. BMD assessment using DEXA scan at the lumbar spine revealed that only one woman had a normal BMD, while 65% (26 out of 40) were diagnosed with severe osteoporosis. These findings highlight a high prevalence of both vitamin D deficiency and osteoporosis among postmenopausal women in the studied population.